Reflexão do papel do estágio curricular supervisionado na formação profissional na licenciatura em educação física - Adamecz Filho, Francisco (2019)
Introduction: A supervised practice in basic education scholls is part of the curriculum of physical education colleges and provides students with observation and reflection of the professional reality in pedagogical and social aspects, articulating theory and practice. Objective: To evaluate the perceptions of the students of physical education about the supervised practice. Materials and Methods: The study population consisted of 15 students from the 6th semester of the graduation course in Physical Education. An interview was conducted based on a questionnaire with open questions. The questions were about the perception of the role of the supervised practice in professional training, relationship between theory and practice, and the relationship among physical professional with the other professional of the school units. Data analysis was done using the content analysis method. Result: With the interview transcriptions, 6 categories were created. For each of them, excerpts from the interviews were taken to generate a material consistent with the student’s reflection. Conclusion: All the students pointed to the importance of the supervised practice for the professional formation. However, some students demonstrated in their speeches dissatisfaction in relation to the observed contents, the work of some professional supervisors, the integration of Physical Education within the school and also, the lack of opportunity to teach during the activies